2021
DOI: 10.1186/s12902-021-00839-x
|View full text |Cite
|
Sign up to set email alerts
|

A challenging TSH/GH co-secreting pituitary adenoma with concomitant thyroid cancer; a case report and literature review

Abstract: Background Thyroid stimulating hormone (TSH) secreting pituitary adenoma (TSHoma) with coexisting thyroid cancer is extremely rare, and proper treatment of both diseases may pose a unique clinical challenge. When TSHoma has plurihormonality, particularly involving the co-secretion of growth hormone (GH), management can be more complicated. Herein, we present a difficult-to-manage case of papillary thyroid cancer with an incurable TSH/GH-secreting pituitary adenoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…All the included GH/TSH cosecreting PAs were macroadenomas, and nearly one-quarter of the PAs were giant adenomas. The mixed PA group presented with a larger median maximum diameter and more cavernous sinus invasion than the age- and sex-matched GH monosecreting PA group, verifying the deductions from a few researchers that PIT-1 lineage plurihormonal PAs are frequently large, and they are also more invasive than mono-secreting PAs ( 12 , 14 , 29 ). The overexpression of PIT-1 is possibly related to cell proliferation in GHPAs, PRLomas and TSHomas, even though the pathophysiological mechanism has not been fully investigated ( 14 , 30 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…All the included GH/TSH cosecreting PAs were macroadenomas, and nearly one-quarter of the PAs were giant adenomas. The mixed PA group presented with a larger median maximum diameter and more cavernous sinus invasion than the age- and sex-matched GH monosecreting PA group, verifying the deductions from a few researchers that PIT-1 lineage plurihormonal PAs are frequently large, and they are also more invasive than mono-secreting PAs ( 12 , 14 , 29 ). The overexpression of PIT-1 is possibly related to cell proliferation in GHPAs, PRLomas and TSHomas, even though the pathophysiological mechanism has not been fully investigated ( 14 , 30 ).…”
Section: Discussionsupporting
confidence: 78%
“…One patient was diagnosed with papillary thyroid carcinoma and underwent thyroid lobectomy. Mixed PAs complicated with thyroid cancer have rarely been reported and are challenging to treat because of the complex interactions between hormones ( 12 , 18 ). Hence, clinicians should be vigilant to screen the thyroid and prevent misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…is is because PAs do not typically present with the typical symptoms that are associated with hormone hypersecretion [6,7]. On the other hand, certain tumors have the potential to spread to the cavernous sinus or the region around the internal carotid artery, making it hard to do a total excision [8]. Surgical treatment is bene cial for NFPAs; however, complete removal of certain tumors is not achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated a potential correlation between TSH and the risk of thyroid cancer[ 27 ]. Elevated TSH levels are considered a risk factor for thyroid cancer as they can stimulate the proliferation and malignant transformation of thyroid cells[ 28 ]. However, not all studies have yielded consistent results, and some studies have failed to establish a conclusive association between TSH and thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%